Pulmonary Vein Antrum Isolation in Patients With Paroxysmal Atrial Fibrillation: More Than a Decade of Follow-Up. (May 2016) - Gökoğlan, Yalçin; Mohanty, Sanghamitra; Güneş, Mahmut F.; Trivedi, Chintan; Santangeli, Pasquale; Gianni, Carola; Asfour, Issa K.; Bai, Rong; Burkhardt, J. David; Horton, Rodney; Sanchez, Javier; Hao, Steven; et al.
Abstract : Background—: We report the outcome of pulmonary vein (PV) antrum isolation in paroxysmal atrial fibrillation (AF) patients over more than a decade of follow-up. Methods and Results—: A total of 513 paroxysmal AF patients (age 54±11 years, 73% males) undergoing catheter ablation at our institutions were included in this analysis. PV antrum isolation extended to the posterior wall between PVs plus empirical isolation of the superior vena cava was performed in all. Non-PV triggers were targeted during repeat procedure(s). Follow-up was performed quarterly for the first year and every 6 to 9 months thereafter. The outcome of this study was freedom from recurrent AF/atrial tachycardia. At 12 years, single-procedure arrhythmia-free survival was achieved in 58.7% of patients. Overall, the rate of recurrent arrhythmia (AF/atrial tachycardia) was 21% at 1 year, 11% between 1 and 3 years, 4% between 3 and 6 years, and 5.3% between 6 and 12 years. Repeat procedure was performed in 74% of patients. Reconnection in the PV antrum was found in 31% of patients after a single procedure and in no patients after 2 procedures. Non-PV triggers were found and targeted in all patients presenting with recurrent arrhythmia after ≥2 procedures. At 12 years, after multiple procedures, freedom from recurrent AF/atrial tachycardia was achieved in 87%. Conclusions—: In patients with paroxysmal AF undergoing extended PV antrum isolation, the rate of late recurrence is lower than what previously reported with segmental or less extensive antral isolation. However, over more than a decade of follow-up, nearly 14% of patients developed recurrence because of new non-PV triggers.